Understanding how human rights law affects nursing practice. (8th April 2021) - Griffith, Richard
Abstract : In the first of a series of articles Richard Griffith, Senior Lecturer in Health Law at Swansea University, discusses the fundamental nature of human rights and their importance to nursing